Physical activities according to playing positions, match outcome, and halves during the 2018 Soccer World Cup - Ugalde-Ramirez, A. (Journal of Physical Education and Sport, 2020)
The objective of this study was to compare the physical activities according to playing positions, match outcomes, and halves during the 2018 Soccer World Cup. The data reported by FIFA were used. Only players who played at least 90 min of the match were included. A total of 866 observations of 8 physical activities [i.e., total distance covered (m/min), distance covered (m/min) at different intensities: standing (<7 km/h), walking (7- 15 km/h), jogging (15-20 km/h), running (20-25 km/h), high-speed running (>25 km/h), maximal speed (km/h), and quantity of sprints per match] were analyzed by a three-way ANOVA that considered five playing positions [i.e., central-defender (CD), full-backs (FB), midfielder-central (CM), wide-midfielder (WM), and centerforward (CF)], three match outcomes [i.e., won, lost, or drew], and two halves (i.e., first and second half). The obtained results indicated that WM of the teams that won covered more distance at high-speed running than WM of teams that ended drawing or losing. WM and FB traveled more distance at >25 km/h during both halves. The maximal speed of CD was lower when teams won compared to CD of losing teams. The players of winning teams covered more distance at <7 km/h during the two halves. Distance covered at 7-15 and 15-20 km/h intensities decreased during the seconds half for all playing positions; when teams drew or lost, the players covered less distance at >25 km/h during the second half. In conclusion, playing positions, match outcomes, and halves affect high-speed activities in modern soccer. High-speed running performed by players of lateral positions may differentiate team performance. This information can help to design and plan training for international tournaments.